Cardiac immune cell infiltration associates with abnormal lipid metabolism - Vincenza Cifarelli; Vincenza Cifarelli; Ondrej Kuda; Kui Yang; Kui Yang; Xinping Liu; Richard W. Gross; Terri A. Pietka; Gyu Seong Heo; Deborah Sultan; Hannah Luehmann; Josie Lesser; et al. (Frontiers in Cardiovascular Medicine, 2022)
CD36 mediates the uptake of long-chain fatty acids (FAs), a major energy substrate for the myocardium. Under excessive FA supply, CD36 can cause cardiac lipid accumulation and inflammation while its deletion reduces heart FA uptake and lipid content and increases glucose utilization. As a result, CD36 was proposed as a therapeutic target for obesity-associated heart disease. However, more recent reports have shown that CD36 deficiency suppresses myocardial flexibility in fuel preference between glucose and FAs, impairing tissue energy balance, while CD36 absence in tissue macrophages reduces efferocytosis and myocardial repair after injury. In line with the latter homeostatic functions, we had previously reported that CD36–/– mice have chronic subclinical inflammation. Lipids are important for the maintenance of tissue homeostasis and there is limited information on heart lipid metabolism in CD36 deficiency. Here, we document in the hearts of unchallenged CD36–/– mice abnormalities in the metabolism of triglycerides, plasmalogens, cardiolipins, acylcarnitines, and arachidonic acid, and the altered remodeling of these lipids in response to an overnight fast. The hearts were examined for evidence of inflammation by monitoring the presence of neutrophils and pro-inflammatory monocytes/macrophages using the respective positron emission tomography (PET) tracers, 64Cu-AMD3100 and 68Ga-DOTA-ECL1i. We detected significant immune cell infiltration in unchallenged CD36–/– hearts as compared with controls and immune infiltration was also observed in hearts of mice with cardiomyocyte-specific CD36 deficiency. Together, the data show that the CD36–/– heart is in a non-homeostatic state that could compromise its stress response. Non-invasive immune cell monitoring in humans with partial or total CD36 deficiency could help evaluate the risk of impaired heart remodeling and disease.